1998
DOI: 10.1152/jn.1998.80.2.863
|View full text |Cite
|
Sign up to set email alerts
|

Codes for Sound-Source Location in Nontonotopic Auditory Cortex

Abstract: We evaluated two hypothetical codes for sound-source location in the auditory cortex. The topographical code assumed that single neurons are selective for particular locations and that sound-source locations are coded by the cortical location of small populations of maximally activated neurons. The distributed code assumed that the responses of individual neurons can carry information about locations throughout 360 degrees of azimuth and that accurate sound localization derives from information that is distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
175
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 144 publications
(198 citation statements)
references
References 48 publications
20
175
1
2
Order By: Relevance
“…The anterior bank of the PSSC projects to the superior colliculus (Bajo et al, 2010a), and is likely to be homologous to the anterior ectosylvian sulcal field (fAES) of the cat (Jiang et al, 1996; Manger et al, 2005). In accordance with the suggestion that cat fAES may be specialized for spatial processing (Middlebrooks et al, 1998; Malhotra and Lomber, 2007; Las et al, 2008), it has been shown that inputs to the aPSSC from the visual cortex arise predominantly from area SSY (Bizley et al, 2007a), which is thought to be specialized for visual motion processing (Philipp et al, 2006). Previous studies of the PSSC have not demarcated the anterior and posterior banks.…”
Section: Discussionsupporting
confidence: 57%
“…The anterior bank of the PSSC projects to the superior colliculus (Bajo et al, 2010a), and is likely to be homologous to the anterior ectosylvian sulcal field (fAES) of the cat (Jiang et al, 1996; Manger et al, 2005). In accordance with the suggestion that cat fAES may be specialized for spatial processing (Middlebrooks et al, 1998; Malhotra and Lomber, 2007; Las et al, 2008), it has been shown that inputs to the aPSSC from the visual cortex arise predominantly from area SSY (Bizley et al, 2007a), which is thought to be specialized for visual motion processing (Philipp et al, 2006). Previous studies of the PSSC have not demarcated the anterior and posterior banks.…”
Section: Discussionsupporting
confidence: 57%
“…Spatial profiles of units can show two or more discrete peaks separated by welldefined valleys, as seen in Figs. 1A and B. Middlebrooks and colleagues [18] found that ∼ 20% units in area A2 and AES had two or more peaks.…”
Section: Neuronal Spatial Tuning and Cortical Topographymentioning
confidence: 98%
“…Spatial sensitivity tends to be broad. For instance, 58 to 97% of units in areas A2 and AES responded with more than 50% of their maximum spike rates across receptive fields spanning 180 • or greater [18]; the exact percentage of units varied with cortical area and sound level. A similar breadth of sensitivity is reported for the majority of units in area A1 [13,15,16].…”
Section: Neuronal Spatial Tuning and Cortical Topographymentioning
confidence: 99%
See 2 more Smart Citations